Tonsillar Cancer with High CD8+ T-Cell Infiltration Features Increased Levels of Dendritic Cells and Transcriptional Regulation Associated with an Inflamed Tumor Microenvironment - David Gomez Jimenez (MDPI AG, 2021)
Human papillomavirus (HPV) is the main causal agent of tonsillar cancer (TC) and HPV+ TC has a favorable prognosis compared to HPV− disease. In this study, we examined aspects of the tumor microenvironment of TC, focusing on T-cells, dendritic cells (DC), and macrophages. Fresh biopsies of TC and the contralateral healthy tonsil (HT) were obtained from 20 patients, analyzed by multiparameter flow cytometry, and assessed against a detailed HPV-status. Additionally, RNA-sequencing data from 38 TC samples available in the public database, The Cancer Genome Atlas (TCGA), were explored, focusing on the same leukocyte populations. HPV+ TC featured increased levels of CD8+ T-cells and antigen-presenting cells (cf. HPV− TC and HT, respectively). In HPV+ TC, CD8+ T-cell frequencies correlated to DC levels independently of tumor stage, HPV 16 copy number, and E7 oncogene expression as well as frequencies of other leukocytes. Similarly, RNA sequencing data were explored by dividing the HPV+ TCs according to predefined CD8+ T-cell scores in silico. Higher levels of genes expressed by antigen-presenting cells and effector T-cells, such as immune checkpoints and cytokines, were detected in the CD8HIGH HPV+ TC samples (cf. CD8LOW HPV+ TC). In conclusion, CD8HIGH HPV+ TC displays a unique inflammatory profile associated with increased effector T-cell functions and the presence of antigen-presenting cells in the tumor microenvironment. Further studies are warranted to assess if this information can be used on an individual basis to aid in prognosis and treatment decisions.